PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI KECAMATAN PAYAKUMBUH UTARA KOTA PAYAKUMBUH - Dasep Suryanto (Jurnal Apresiasi Ekonomi, 2020)
ABSTRACT This study aims to look at "The influence of leadership and motivation on the performance of North Payakumbuh District Payakumbuh employees". The total population and sample in this study were all employees in the North Payakumbuh District Payakumbuh City through the distribution of questionnaires with a Likert scale model then tested the validity and reliability of the questionnaire. The data analysis technique used is the Multiple Linear Regression Analysis method, after passing the classical assumption test using the SPSS program. In this study leadership (X1) and motivation (X2) as independent variables, performance (Y) as the dependent variable. The results of this study are a). Leadership has a positive and significant effect on the performance of North Payakumbuh District Payakumbuh employees that is equal to 0.222 with a significance level of 0.026 <0.05. b). Motivation has a positive and significant effect on the performance of North Payakumbuh District Payakumbuh employees that is equal to 0.782 with a significance level of 0,000 <0.05, leadership and motivation together have a significant positive effect on the performance of North Payakumbuh District Payakumbuh City employees at 51,623 with a significance level of 0,000 <0 .5. Based on the conclusions obtained, it is recommended to further researchers, if you want to do similar research, it is expected to add other factors that can affect employee performance such as incentives, work environment, and others. Keywords: Leadership; Performance; Motivation